2023
DOI: 10.3390/antiox12020254
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Alpha-Glucosidase Inhibition Activities, In Silico Molecular Docking and Pharmacokinetics Study of Phenolic Compounds from Native Australian Fruits and Spices

Abstract: Native Australian fruits and spices are enriched with beneficial phytochemicals, especially phenolic compounds, which are not fully elucidated. Therefore, this study aimed to analyze native Australian mountain-pepper berries (Tasmannia lanceolata), rosella (Hibiscus sabdariffa), lemon aspen (Acronychia acidula), and strawberry gum (Eucalyptus olida) for phenolic and non-phenolic metabolites and their antioxidant and alpha-glucosidase inhibition activities. Liquid chromatography–mass spectrometry–electrospray i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…The use of computational methods has been increased to test the bioactive potential of the target compounds. In silico molecular docking helps to understand bioactive compounds’ behavior in the HPPD protein’s binding sites [ 100 ]. In this sense, in the docking study, the binding energies of the major constituents of the EOs ranged from −7.8 to −5.2 kcal/mol, indicating moderate to good inhibition of the enzyme ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The use of computational methods has been increased to test the bioactive potential of the target compounds. In silico molecular docking helps to understand bioactive compounds’ behavior in the HPPD protein’s binding sites [ 100 ]. In this sense, in the docking study, the binding energies of the major constituents of the EOs ranged from −7.8 to −5.2 kcal/mol, indicating moderate to good inhibition of the enzyme ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, many studies showed that phenolic content correlate directly with anti-diabetic activity. [68][69][70] Flavonoids are a diverse category of organic compounds that are mostly present in fruits, vegetables, nuts, tea, and herbs. 71 Earlier research showed that the majority of dietary flavonoids had a range of health benefits, including acting as anti-hyperglycemic agents, 72,73 Recent research on saponins has shown that these plant-derived chemicals have the ability to increase insulin release and reduce glucose absorption by acting through the AMP-activated protein kinase (AMPK) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, the total phenol content was found to be 57.13 ± 0.0255 mg g −1 and showed positive correlation between phenol content and anti‐diabetic effect. Similarly, many studies showed that phenolic content correlate directly with anti‐diabetic activity 68–70 . Flavonoids are a diverse category of organic compounds that are mostly present in fruits, vegetables, nuts, tea, and herbs 71 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Zn 2+ metal ion is a distinctive component of the α, β, and δ type gene families; the family of CAs is saturated with Zn 2+ , Fe 2+ , and Co 2+ metal ions, whereas the ζ‐CAs family is rich in Zn 2+ or Cd 2+ in the catalytic domains. [ 33,34 ] Mammals have 16 different types of CA isoforms that are either membrane‐bound (CA II, CA V, CA XII, CA XV, and CA XIV) or found in the cytosol (CA I, CA II, CA III, CA VII, and CA XIII) or present in the mitochondria (CA VA and CA VB). Numerous physiological processes, including pH control, respiration, the secretion of electrolytes, bone resorption, Na + ion retention, signal transduction, lipogenesis, ureagenesis, and gluconeogenesis, are all thought to be affected by the roles played by CAs.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] Molecular docking, a computational method that predicts the binding mode and affinity between a small molecule, typically a drug candidate, and a receptor, such as a protein target or a nucleic acid, has emerged as an indispensable tool in the field of drug discovery due to its high significance and versatility. [33,34] It provides a rational and efficient approach for identifying and optimizing potential drug candidates by predicting their interactions with the target biomolecule. Molecular docking is recommended as an alternative strategy to the traditional in vitro screening methods, which are costly, time-consuming, and often limited to a few compounds.…”
mentioning
confidence: 99%